Management of Fallopian Tube Cancer - Rai, Shweta; Maheshwari, Amita (Reviews on Recent Clinical Trials, 2015)
Primary Fallopian Tube Carcinomas are rare and share many clinical and histo- pathological features with primary peritoneal and high grade serous carcinomas of ovary. The three have a considerable overlap in pathogenesis and clinical course leading to the view of them being a single entity. Due to the same reason, International Federation of Obstetrics and Gynecology (FIGO) 2014, in the latest staging have staged them collectively with the clause of designating the primary wherever possible. Presenting symptoms of fallopian tube carcinoma are vague. The diagnosis is generally made in retrospect in women operated for adnexal mass. Imaging studies have not shown to be of much help in pre-operative diagnosis. Management strategies are same for all three regardless of their ovarian, tubal, or peritoneal derivation. Due to rarity, no randomized trials are available exclusively for FTC and most treatment strategies have been extrapolated from epithelial ovarian cancers. In recent times, there has been a rapidly increasing body of evidence supporting the tubal origin for all high grade serous carcinomas of ovary. This has led to growing interest in the strategy of prophylactic salpingectomy rather than salpingooophorectomy as a preventive measure for ovarian carcinomas.
Keywords: salpingo-oophorectomy